2015
DOI: 10.13189/ujer.2015.031201
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Cyberbullying and the Views of 5-12 Grade Pupils and Teachers on Cyberbullying Prevention in Lithuanian Schools

Abstract: This article analyses the views of cyberbullying prevention among 5-12 grade pupils and teachers in Lithuanian schools. It defines the concept of cyberbullying in the context of school pupils, and analyses the theoretical grounds for prevention of this form of bullying. The article also presents the results of the survey (which was conducted in [2009][2010] and reveals the views of 2064 pupils of 5 -12 grade and their 1062 teachers towards the prevention of cyberbullying. Based on the empirical research, it co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…The studies identified in Table 1 were conducted in the UK (n = 3) (Betts & Spenser, 2015;Boulton et al, 2014;Monks, Mahdavi, & Rix 2016), USA (n = 3) (Pelfrey & Weber, 2015;Stauffer et al, 2012;Styron et al, 2016) and Canada (n = 3) (Cassidy, Brown, & Jackson, 2012;Li, 2008;Ryan, Kariuki, & Yilmaz, 2011). The other studies identified represented Australia (n = 2) ( Barnes et al, 2012;Compton, Campbell, & Mergler, 2014), Turkey (n = 2) (Sezer, Yilmaz, & Yilmaz, 2015;Yilmaz, 2010) and Belgium (n = 2) (DeSmet et al, 2015;Vandebosch, Poels, & Deboutte, 2014), with one study each representing Lithuania (Baraldsnes, 2015), Israel (Eden, Heiman, & Olenik-Shemesh, 2013), New Zealand (Green et al, 2016), Taiwan (Republic of China) (Huang & Chou, 2013), and Northern Ireland and the Republic of Ireland (Purdy & Mc Guckin, 2015). Thirteen of the twenty studies utilised a survey methodology, with four taking a qualitative approach through focus groups (Betts & Spenser, 2015;Compton, Campbell, & Mergler, 2014;Monks, Mahdavi, & Rix, 2016) or interviews (Pelfrey & Weber, 2015).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies identified in Table 1 were conducted in the UK (n = 3) (Betts & Spenser, 2015;Boulton et al, 2014;Monks, Mahdavi, & Rix 2016), USA (n = 3) (Pelfrey & Weber, 2015;Stauffer et al, 2012;Styron et al, 2016) and Canada (n = 3) (Cassidy, Brown, & Jackson, 2012;Li, 2008;Ryan, Kariuki, & Yilmaz, 2011). The other studies identified represented Australia (n = 2) ( Barnes et al, 2012;Compton, Campbell, & Mergler, 2014), Turkey (n = 2) (Sezer, Yilmaz, & Yilmaz, 2015;Yilmaz, 2010) and Belgium (n = 2) (DeSmet et al, 2015;Vandebosch, Poels, & Deboutte, 2014), with one study each representing Lithuania (Baraldsnes, 2015), Israel (Eden, Heiman, & Olenik-Shemesh, 2013), New Zealand (Green et al, 2016), Taiwan (Republic of China) (Huang & Chou, 2013), and Northern Ireland and the Republic of Ireland (Purdy & Mc Guckin, 2015). Thirteen of the twenty studies utilised a survey methodology, with four taking a qualitative approach through focus groups (Betts & Spenser, 2015;Compton, Campbell, & Mergler, 2014;Monks, Mahdavi, & Rix, 2016) or interviews (Pelfrey & Weber, 2015).…”
Section: Search Resultsmentioning
confidence: 99%
“…This suggests additional guidance should be provided to encourage young people to be responsible when using the internet. In-service teachers have also recommended advice for the victim (69.5%), professional support (37%) (DeSmet et al, 2015), promoting school culture (70.12%) (Baraldsnes, 2015), cyberbullying education (Pelfrey & Weber, 2015), and staff supervision (77%) ( Barnes et al, 2012) as effective preventive strategies to manage cyberbullying. While teachers are inevitably unable to manage all cyberspace interactions to reduce cyberbullying involvement, with a collaborative approach it can be possible to promote a stronger sense of belonging through a positive school culture, in the hope to reduce cyberbullying involvement.…”
Section: School Commitment and Strategies To Manage Cyberbullyingmentioning
confidence: 99%
See 1 more Smart Citation
“…This line focuses on the study of the profile of the aggressor (addiction, aggressiveness, anonymity, antisocial behaviour, or feeding behaviour), of the victim (anxiety, body image, fear, family, education status, emotion, or psychological well-being), of diseases and associated disorders (comorbidity, anxiety, mental disease, mental disorder, mental health, mental stress, disease association, or distress syndrome), or the analysis of this type of aggression (coping behaviour, cyber aggression, cyber harassment, cyber victimization, cyberbullying perpetration, cyberbullying victimization, or drug dependency). This thematic axis in studies the significant impact that CB has on the psychosocial adjustment of adolescents, which increases depressive symptoms and the problematic use of the Internet and social networks [128,129]. The second line associated with the term student, is related to the study, mainly, of the influence of CB on academic self-esteem and school perception (college student, education, organization, organization and management, school health service, school teacher, primary school, or secondary education).…”
Section: Analysis Of Abstractmentioning
confidence: 99%
“…There are discrepancies beyond their conceptualization of cyberbullying (Compton et al 2014). Baraldsnes (2015) evidenced that even teachers' and pupils' perceptions regarding cyberbullying frequency are quite different. As a result, there have been successive studies, although they are scarce today, involving in-service teachers and pre-service teachers.…”
Section: Introductionmentioning
confidence: 99%